An ecological assessment of Hispid Hare Caprolagus hispidus (Mammalia: Lagomorpha: Leporidae) in Manas National Park, Assam, India - Naba K. Nath; Kamal Machary (Journal of Threatened Taxa, 2015)
This study of the Hispid Hare Caprolagus hispidus in the tall grassland habitat of Manas National Park, Assam during 2009–2010 is the first detailed assessment in northeastern India.  We assessed the status, distribution, habitat use and key threats to this rare and little studied lagomorph species.  After interviewing local forest staff, 20 grassland patches within a survey area of 2.65ha were selected and transects (50x2 m) laid randomly to determine the presence/absence of Hispid Hare by recording pellets and other indirect evidence.  Hare presence was recorded in 17 grassland patches within transects dominated by Imperata cylindrica and Saccharum narenga.  Hispid Hare preferred dry savannah grasslands to wet alluvial grasslands during winter and avoided recently burned patches due to lack of cover and food.  The distribution pattern observed was clumped (s2/a = 6.2), with more evidence of Hispid Hare presence in areas where ground cover was dense, dry and away from water sources. Population density was estimated at 381.55 individuals/km2, which in comparison with other studies indicates that Manas National Park currently holds the highest density of Hispid Hare.  Habitat loss due to overgrazing, unsustainable thatch harvesting, burning of grassland, weed invasion, encroachment and hunting were identified as key threats which must be addressed to ensure survival of this threatened species in the Park.